Retraction: Traditional methods used by mothers living in different regions of turkey for increasing breast milk supply and weaning - Tural Büyük, Esra (Progress in Nutrition, 2021)
Background: It is a known fact that traditional practices mothers use in increasing breast milksupply and weaning differ in different parts of countries and even among communities sharing the same city.This study was conducted to find out the use of herbal tea and some foods to increase breast milk, the traditional methods used for weaning and the factors influencing these.Methods: This study is descriptive and cross-sectional. Three cities in Turkey with different levels of development in terms of geographical and socio economic regions were chosenThe data of the study were collected through a questionnaire form developed by the researchers.Results: It was found that the mothers who received breast milk increasing training the most were in easternregion, while mothers in western region fed their babies with formula since they thought their milk was notenough and this result was found to be statistically significant (p